2006
DOI: 10.1007/s11119-006-9004-y
|View full text |Cite
|
Sign up to set email alerts
|

Identifying important factors influencing corn yield and grain quality variability using artificial neural networks

Abstract: Soil, landscape and hybrid factors are known to influence yield and quality of corn (Zea mays L.). This study employed artificial neural network (ANN) analysis to evaluate the relative importance of selected soil, landscape and seed hybrid factors on yield and grain quality in two Illinois, USA fields. About 7 to 13 important factors were identified that could explain from 61% to 99% of the observed yield or quality variability in the study site-years. Hybrid was found to be the most important factor overall f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(61 citation statements)
references
References 28 publications
1
53
0
2
Order By: Relevance
“…Even for the ANN with 6 input variables, the results also were superior to those of the MLR with 10 input variables. The result was similar to the findings of Kaul et al (2005) and Miao et al (2006). Kaul et al (2005) used both soil productivity rates and climate variables for yield prediction and found that ANN had shown to be better tools than regression methods when analyzing corn and soybean yield data generated in field trials.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Even for the ANN with 6 input variables, the results also were superior to those of the MLR with 10 input variables. The result was similar to the findings of Kaul et al (2005) and Miao et al (2006). Kaul et al (2005) used both soil productivity rates and climate variables for yield prediction and found that ANN had shown to be better tools than regression methods when analyzing corn and soybean yield data generated in field trials.…”
Section: Discussionsupporting
confidence: 81%
“…Kaul et al (2005) used both soil productivity rates and climate variables for yield prediction and found that ANN had shown to be better tools than regression methods when analyzing corn and soybean yield data generated in field trials. Miao et al (2006) employed ANN analysis to evaluate the relative importance of selected soil, landscape and seed hybrid factors on corn yield and grain quality in two Illinois, USA fields, and the results indicated that the response curves generated by the ANN models were more informative than simple correlation coefficients or coefficients in multiple regression equation. The performance of ANN in the study was mainly attributed to the ability of ANNs to capture the nonlinear input-output relationship between crop growth and soil moisture and salinity, whereas MLRs were unable to reflect these complicated relationships due to their linear characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…A ratio greater than 1.0 implied that, then, the variable made an important contribution to the variability in soil organic matter. The higher the ratio, the more important the variable (StatSoft, 2004;Miao, 2006).…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…[20][21][22][23][24] This paper presents the development of an ANN calibration model to determine aluminum in the presence of iron in soil extracts, without any additional sample treatment, using the molecular spectral data of the complexes Al-XO and Fe-XO in the visible region. The ANN prediction ability was evaluated by comparison with ICP OES measurements.…”
Section: Introductionmentioning
confidence: 99%